Ioakeim Kyprios’ Struggle and the Story of the Maltese Sultana: A Literary Account of Historical Events? - Kaplanis, Tassos A. (Études helléniques / Hellenic Studies, 2007)
The personality and work of Ioakeim Kyprios are not yet well known by contemporary scholars.The author of this article discusses a long narrative poem written by Ioakeim about the Turco-Venetian conflict of 1645-1669. More precisely, he ponders whether this poem presents the story of the Maltese Sultana.